Long‐term GPi‐DBS improves motor features in myoclonus‐dystonia and enhances social adjustment. Issue 1 (9th October 2018) - Kosutzka, Zuzana; Tisch, Stephen; Bonnet, Cecilia; Ruiz, Marta; Hainque, Elodie; Welter, Marie‐Laure; Viallet, Francois; Karachi, Carine; Navarro, Soledad; Jahanshahi, Marjan; Rivaud‐Pechoux, Sophie; Grabli, David; et al.
ABSTRACT: Background: Good short‐term results of pallidal deep brain stimulation have been reported in myoclonus‐dystonia. Efficacy and safety in the long term remain to be established. In addition, the actual impact of DBS treatment on social inclusion is unknown. The objective of this study was to assess the long‐term clinical outcome, quality of life, and social adjustment of GPi‐DBS in patients with ε‐sarcoglycan (DYT11)‐positive myoclonus‐dystonia. Methods: Consecutive myoclonus‐dystonia patients with ε‐sarcoglycan mutations who underwent GPi‐DBS were evaluated at least 5 years postoperatively. Motor symptoms were assessed using the Burke‐Fahn‐Marsden Dystonia Rating Scale including the Disability Scale, a composite score combining the rest and action parts of the Unified Myoclonus Rating Scale and modified Abnormal Involuntary Movement Scale. Standardized video‐protocols were assessed by a blinded and external movement disorder specialist. Social adjustment, cognition, and mood were evaluated. Results: Nine patients (5 women) with long‐term GPi‐DBS (8.7 ± 3.1 years) were included. There was significant improvement in the composite myoclonus score (94.1% ± 4% improvement; P  = 0.008). Dystonia severity was also markedly improved (71.4% ± 28.33% improvement; P  = 0.008) as well as motor disability (88.3% ± 20% improvement; P  = 0.008) and abnormal involuntary movement score (71.1% ± 15.0% improvement; P  = 0.008). No patients experienced postoperative speech or gait problems or any permanent adverse effects. Eight of the 9 patients had fully enhanced social adjustment and personal achievement, with little or no mood or behavioral disorders. Conclusions: GPi‐DBS seems to be a safe and efficacious treatment for medically refractory ɛ‐sarcoglycan myoclonus‐dystonia, with sustained motor benefit, good quality of life, and social adjustment in long‐term follow‐up. © 2018 International Parkinson and Movement Disorder Society